« Cette femme éminente a touché l’âme universelle ». Une théorie médicale du talent de l’actrice-chanteuse dans La Pasta nell’Otello de Luigi Morando De Rizzoni (Vérone, Crescini, 1830) - Céline Frigau Manning (Laboratoire Italien)
Luigi Morando De Rizzoni’s fictional dialogue La Pasta nell’Otello was published in Verona following Giuditta Pasta’s tour of northern Italy during the winter of 1829-1830. Five characters spend their evening debating the singer’s talent, its causes and effects. Explicitly taking the side of the singer, the dialogue’s author, a wine producer and the brother of a doctor, provides us with a fascinating text, both from the perspective of the opinions and accounts which he develops concerning Giuditta Pasta’s singing and acting in Rossini’s Otello, as well as the elements of aesthetic and medical theories which he integrates into his arguments. Indeed, the dialogue aims at establishing a universal aesthetic judgment on man’s physiological nature, and the physical and moral effect on this nature which Giuditta Pasta, perceived as being exceptional, produces. In this way, contrary to erudite criticism – above all attentive to technical and musical aspects – De Rizzoni proposes a theory of aesthetic reception based on the communication of passions. The following text is the full translation of this document, previously unpublished in French.